2004
DOI: 10.1088/0022-3727/37/21/008
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of pulsed dielectric barrier discharge xenon excimer lamp

Abstract: Recently, it has been shown that the efficiency of excimer lamps can be drastically increased in a pulsed regime. A one-dimensional simulation of pulsed excimer lamps has been performed by Carman and Mildren (2003 J. Phys. D: Appl. Phys. 36 19) (C&M). However, some computational results of the work of C&M are questionable and need to be revisited. In this paper, a dielectric barrier discharge (DBD) in xenon has been simulated for operating conditions similar to those of C&M to better understand plasma dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…It is instructive to note that under these operating conditions of the DBDs, the breakdown occurs rapidly and high energy is deposited in the plasma medium by electrons. Recent investigations [21,24,37,39,40] showed that the use of short pulse with a fast Table 1 List of reaction processes and their rate coefficients used in the present work (T e is the electron temperature)…”
Section: Discharge Processmentioning
confidence: 99%
See 2 more Smart Citations
“…It is instructive to note that under these operating conditions of the DBDs, the breakdown occurs rapidly and high energy is deposited in the plasma medium by electrons. Recent investigations [21,24,37,39,40] showed that the use of short pulse with a fast Table 1 List of reaction processes and their rate coefficients used in the present work (T e is the electron temperature)…”
Section: Discharge Processmentioning
confidence: 99%
“…It has been investigated using many different excited species, including rare gas excimers, molecular rare gas-halide excimers, and halogen dimers [1,[11][12][13][14][15][16][17]. In particularly, excimer and exciplex lamps are predestined for the lighting industry with a long lifetime (up to 4,000 h), as the current is limited by the dielectric and the working mixture does not have a contact with metal electrodes which avoids any reaction between the discharge and the electrodes or contamination of the gas with evaporated electrode material [2,[18][19][20][21][22][23][24][25]. However, the kinetic processes in the plasma responsible for the enhanced lamp performance and increased efficiency are not well understood and the principal disadvantage of excimer DBD discharge is especially their low efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, a secondary emission coefficient [24,47,60,61,74] of 0.25 has been assumed for neon ions. Usually, in DBD's configuration for display panels or lamps a MgO thin film is deposited above the dielectric layers in order to protect the dielectric layers, and decrease the breakdown voltage due to the relatively large value of the secondary electron emission coefficient of MgO bombardment by neon ions.…”
Section: Discharge Behaviormentioning
confidence: 99%
“…The model used by Carman et al [22,49,50] analyzes the spatiotemporal evolution of species populations and electrical parameters. Also, in order to investigate the spatiotemporal characteristics of the short-pulsed DBDs in pure xenon, a 1D and 2D fluid models was used by Bogdanov et al [24,51]. S. Belezenai et al in Ref.…”
Section: Introductionmentioning
confidence: 99%